2023
DOI: 10.1161/jaha.122.025438
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Visit‐to‐Visit Glycemic Variability as a Predictor of Major Adverse Limb and Cardiovascular Events in Patients With Diabetes

Abstract: Background Peripheral arterial disease (PAD) is a severe complication in patients with type 2 diabetes. Glycemic variability (GV) is associated with increased risks of developing microvascular and macrovascular diseases. However, few studies have focused on the association between GV and PAD. Methods and Results This cohort study used a database maintained by the National Taiwan University Hospital, a tertiary medical center in Taiwan. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
2
7
1
1
Order By: Relevance
“…The present results were in line with those from previous observational studies, which reported the association of high HbA1c variability and increased cardiovascular complications, including coronary events, heart failure, microvascular diseases, stroke, major adverse limb events, cardiovascular mortality, non-cardiovascular mortality and all-cause mortality 7,8,21 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present results were in line with those from previous observational studies, which reported the association of high HbA1c variability and increased cardiovascular complications, including coronary events, heart failure, microvascular diseases, stroke, major adverse limb events, cardiovascular mortality, non-cardiovascular mortality and all-cause mortality 7,8,21 .…”
Section: Discussionsupporting
confidence: 93%
“…However, the present study showed a very high magnitude of increased risk of developing myocardial infarction by 6.9-fold, increased risk of all-cause death by 3.1fold and increased risk of heart failure by 3.3-fold in the highest quartile compared with the lowest quartile of HbA1c variability, which is greater than other studies that found only 1.2-2-fold the increased risk 7,8,21 . This difference could be explained by the fact that the two studies by Hsu et al 8 and Ceriello et al 21 excluded all diabetes patients with established ASCVD from the cohort, whereas in the present study, all diabetes participants, with or without established ASCVD, were included 8,21 . It is possible that patients who have previously had ASCVD might be at a higher risk of developing new events of cardiovascular disease compared with those without previous ASCVD.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Glycemic fluctuation and chronic hyperglycemia can trigger an inflammatory response, and GV has adverse effects on autonomic function and increases thrombogenicity, leading to the development of macrovascular disease. A cohort study [ 18 ] on 45 436 patients with prevalent type 2 diabetes investigated the relationship between GV and the occurrence of major adverse limb events (MALEs), and the impacts of GV on major adverse cardiovascular events (MACEs) in patients with diabetes. The study concluded that in patients with diabetes, higher GV led to a significantly increased risk of MALEs compared with lower GV, largely driven by the increased development of PAD and CLI.…”
Section: Introductionmentioning
confidence: 99%